Comparison of Risk Factors, Prevalence, Type of Treatment, and Mortality Rate for Myocardial Infarction in Diabetic and Non-diabetic Older Adults: A Cohort Study - Parisa Janjani; Yaser Salehabadi; Sayeh Motevaseli; Reza Heidari Moghadam; Soraya Siabani; Nahid Salehi (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Older diabetic patients with myocardial infarction (MI) are vulnerable group. This study aims to compare the prevalence of risk factors, type of reperfusion therapy, and mortality in diabetic and non-diabetic elderly with MI. Methods & Materials This is a cohort study. The statistical population consists of all older adults (age ≥60 years), whose information was available in the ST-segment elevation myocardial infarction (STEMI) registry system of Imam Ali hospital in Kermanshah, Iran from July 2016 to January 2020. Of these, 1460 participants with STEMI were selected based on the inclusion criteria and divided into two diabetic and non-diabetic groups. Their information was recorded by trained nurses using a checklist surveying demographic information, medical records, cardiovascular disease risk factors, clinical and diagnostic tests, type of treatment, and death at the time of admission, hospitalization and discharge. Data analysis was performed using descriptive statistics, independent t-test, Mann-Whitney and chi-square test in Stata software, version 14. P<0.05 was considered as significant level. Results The number of diabetic women (47.11%) was significantly higher than the number of those without diabetes (25.60%) (P<0.001). The mean LDL and cholesterol levels in non-diabetics was significantly higher than diabetics (P<0.001). The mean HDL was not significantly different between the two groups (P=0.777). The number of patients with BMI≥30, history of myocardial infarction, blood lipid, hypertension, triglyceride level, and glomerular filtration rate <60 were significantly higher in the diabetic group than in the non-diabetic group. There were no significant differences between the two groups regarding the variables of place of residence, literacy level, smoking, history of stroke, coronary angioplasty and coronary artery bypass surgery. In addition, there was no significant difference in mortality rate and type of reperfusion treatment between the two groups. Conclusion Some of risk factors for MI are different between diabetic and non-diabetic elderly with MI. The results of this study can provide useful information to experts in this field to develop lifestyle modification programs by making drug prescription more purposeful and providing awareness for this group of patients.